Tindak Tutur Ekspresif dalam Lirik Lagu Arab Populer: Analisis Lagu Magadir dan Nur Al-‘Ain - Awliya Rahmi; Wartiman Wartiman; Ahmad Busyrowi (Diwan: Jurnal Bahasa dan Sastra Arab, 2020)
This article aims to describe the function of expressivespeech acts in the lyrics of popular Arabic songs. Thelyrics of the Magadir song sung by Talal Maddah andNur Al-'Ain, sung by Amru Diab, were used as datasources. The data was collected using the uninvolvedconversation observation method. Also, data analysiswas carried out by tracing the qualitative analysisproposed by Miles and Huberman. The researchfindings show that expressive speech acts in the songlyrics of the data sources are broadly divided intoexpressions of sadness and joy. These twoexpressions are built in the context of the speaker andlover's love relationship. From the data analysis, it wasfound that there were 5 functions of expressive speechacts that were more detailed: complaining (3);disappointed (2); hope (1); praise (3); sure (2).